A supported catalyst for dehydrogenating cyclododecanol to ketone, its preparation method and uses
By multiple modifications of the MCM-41 mesoporous molecular sieve support, a supported catalyst containing Ir/Pd composite oxide was prepared, which solved the problem of existing catalysts being corroded and toxic by organic chlorides during the dehydrogenation of cyclododecyl alcohol, and achieved a significant improvement in catalytic activity and service life.
Patent Information
- Application Number
- CN202111573380.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-21
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2041-12-21
AI Technical Summary
The existing catalysts are easily corroded and toxic by organic chlorides during the dehydrogenation of cyclododecanes, resulting in reduced catalytic activity and shortened service life.
The MCM-41 mesoporous molecular sieve support is modified by multiple modifications, including a ZnO layer and an Ir/Pd composite oxide layer on its surface, to improve catalytic activity, corrosion resistance and stability.
It significantly improves the catalytic activity and service life of the catalyst, can effectively adsorb and remove organic chloride impurities, and maintain efficient cyclododecyl conversion and cyclododecyl selectivity.
Smart Images

Figure BDA0003423955070000091 
Figure BDA0003423955070000092 
Figure BDA0003423955070000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst preparation, and particularly to a supported catalyst containing Ir / Pd composite oxide for dehydrogenation of cyclododecanol to ketone, a preparation method thereof and uses, and also relates to a method for preparing cyclododecanone by dehydrogenation of cyclododecanol. Background Art
[0002] Cyclododecanone is an important chemical product, which can be used as a raw material or intermediate in the perfume industry, and is also an important intermediate in the field of engineering plastics, such as for long-chain nylon resins PA12, PA1212, etc. The preparation of cyclododecanone usually uses cyclododecatriene (CDT) as a raw material. First, cyclododecanol (CDOL) is prepared, and then cyclododecanol is dehydrogenated to obtain cyclododecanone product.
[0003] At present, the catalysts used in the reaction of dehydrogenating cyclododecanol to cyclododecanone mainly refer to the catalysts used in dehydrogenating cyclohexanol to cyclohexanone. In China, there are mainly the following two types: the catalyst with Cu as the active component and Al 2 O 3 or SiO 2 as the carrier; the catalyst with Cu as the active component and SiO 2 as the carrier developed by Sun Zhonghua et al. of Sinopec Nanjing Chemical Industry Group. In addition, Chinese Patent CN103055880A discloses a catalyst for dehydrogenating cyclododecanol to ketone, which includes a main catalyst and an auxiliary agent. The main catalyst is a copper-zinc mixed oxide with copper element as the main active ingredient and zinc element as the carrier, and the auxiliary agent is a transition metal element of a non-active center.
[0004] However, in the reaction process of CDT→CDOL, since a metal-based catalyst containing chlorine is usually used, organic chloride impurities are very likely to be generated. This impurity has a strong poisoning effect on the currently used CDOL dehydrogenation reaction catalyst. The content of organic chloride adsorbed by the catalyst during the dehydrogenation reaction can be as high as thousands of ppm. Therefore, it is very easy to shorten the catalyst life and reduce the activity, especially having a greater impact on the selectivity of cyclododecanone.
[0005] Therefore, it is urgent to develop a new type of catalyst that can be used for dehydrogenating cyclododecanol to cyclododecanone, so that it can maintain good catalytic activity while also being able to resist the corrosion and poisoning of organic chlorides, thus having a long service life. Summary of the Invention
[0006] To overcome the deficiencies in the prior art, an object of the present invention is to provide a supported catalyst containing an Ir / Pd composite oxide. By performing multiple modifications on the MCM-41 mesoporous molecular sieve support, the catalytic activity, corrosion resistance, and stability of the obtained catalyst are effectively improved, and thus it is particularly suitable for the reaction of dehydrogenating cyclododecanol to produce ketone.
[0007] Another object of the present invention is to provide a preparation method and use of the supported catalyst.
[0008] Still another object of the present invention is to provide a method for dehydrogenating cyclododecanol to produce ketone.
[0009] The supported catalyst containing an Ir / Pd composite oxide provided by the present invention uses a Fe-MCM-41 mesoporous molecular sieve as the support, a ZnO layer is loaded on the surface of the support, and an Ir / Pd composite oxide layer is loaded on the ZnO layer.
[0010] The supported catalyst provided by the present invention has the following characteristics: (1) Using a Fe-MCM-41 mesoporous molecular sieve as the support, Fe is loaded in the pores of the molecular sieve, increasing the active sites and improving the catalytic activity of the catalyst; (2) The ZnO layer has a dual function of simultaneously adsorbing organic chlorides and regulating the dispersion degree of the Ir / Pd composite oxide. The basic ZnO layer has a strong ability to adsorb organic chlorides and is the main adsorption layer. While removing organic chlorides, it can also prevent them from damaging the molecular sieve support and the active components of the Ir / Pd composite oxide. Secondly, it can prevent the aggregation of the Ir / Pd composite oxide, increase its dispersion degree, thereby increasing the number of its active sites, further improving the catalytic activity and service life of the catalyst. In addition, the ZnO layer can also make the structure of the molecular sieve support more stable and not easily damaged; (3) The Ir / Pd composite oxide layer (IrO 2 -PdO) as the outer layer of the catalyst has good corrosion resistance, can also adsorb some organic chlorides, enhancing the dechlorination effect. In addition, due to the good dispersion degree of the Ir / Pd composite oxide layer, the number of active sites is large and evenly distributed, and the catalytic activity can be significantly enhanced and maintained at a relatively high level for a long time. The supported catalyst provided by the present invention performs multiple modifications on the internal pores and outer layer of the MCM-41 mesoporous molecular sieve support, significantly improving its catalytic activity and service life, and can also effectively adsorb organic chloride impurities and remove them from the reaction system. Therefore, the supported catalyst provided by the present invention is particularly suitable for the reaction of dehydrogenating cyclododecanol to produce ketone.
[0011] In the supported catalyst provided by the present invention, the mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer can be 30-45:8-20:0.5-3. In some preferred embodiments, the mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer can be 30-40:10-20:0.8-2. In some more preferred embodiments, the mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer can be 35-40:10-18:0.8-1.5. In some most preferred embodiments, the mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer can be 36:15:1.
[0012] In the supported catalyst provided by the present invention, in the Ir / Pd composite oxide layer, the molar ratio of Ir to Pd can be 1:1-8, including but not limited to molar ratio values such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or any combined molar ratio range. In some preferred embodiments, the molar ratio of Ir to Pd can be 1:3-6.
[0013] In the supported catalyst provided by the present invention, in the Fe-MCM-41 mesoporous molecular sieve, the mass percentage content of Fe can be 10-25%, including but not limited to mass percentage values such as 10%, 12%, 15%, 18%, 20%, 22%, 25%, or any combined mass percentage range. In some preferred embodiments, the mass percentage content of Fe can be 15-20%.
[0014] The preparation method of the supported catalyst containing the Ir / Pd composite oxide provided by the present invention includes the following steps:
[0015] S1: Using the Fe-MCM-41 mesoporous molecular sieve as a carrier, loading a ZnO layer on its surface; and
[0016] S2: Preparing the Ir / Pd composite oxide and loading it on the ZnO layer to form an Ir / Pd composite oxide layer.
[0017] In the preparation method provided by the present invention, the Fe-MCM-41 mesoporous molecular sieve used in step S1 can be prepared through the following process: using sodium silicate as a raw material, cetyltrimethylammonium bromide (CTAB) as a template agent, and Fe(NO 3 ) 2is a Fe source and is prepared by a hydrothermal reaction. In some preferred embodiments, the temperature of the hydrothermal reaction can be 100 to 150 °C, and the reaction time can be 20 to 40 h. In some other preferred embodiments, after the hydrothermal reaction, the template agent can be removed by calcination, the calcination temperature can be 500 to 800 °C, and the calcination time can be 2 to 5 h.
[0018] In some more preferred embodiments, the Fe-MCM-41 mesoporous molecular sieve can be prepared by the following process:
[0019] (1) Prepare an aqueous sodium silicate solution (solution A), and prepare an aqueous solution of a template agent and a Fe source (solution B);
[0020] (2) Add solution A to solution B, and adjust the pH value of the solution (for example, using 0.5 to 2 mol / L H 2 SO 4 solution) to 9 to 11 (preferably 10) to obtain solution C;
[0021] (3) After stirring solution C for a period of time, for example, it can be stirred for 0.5 to 2 h, transfer it to a hydrothermal reaction kettle for hydrothermal reaction, the reaction temperature can be 100 to 150 °C (preferably 110 to 130 °C), and the reaction time can be 20 to 40 h (preferably 20 to 30 h);
[0022] (4) After separating and washing the solid obtained from the hydrothermal reaction, remove the template agent (for example, by calcination) to obtain the product.
[0023] In the preparation method provided by the present invention, step S1 can be: using Zn(NO 3 ) 2 as the Zn source, carrying out a hydrothermal reaction with the Fe-MCM-41 mesoporous molecular sieve, and then carrying out calcination to load the ZnO layer. In some preferred embodiments, the temperature of the hydrothermal reaction can be 100 to 150 °C, and the reaction time can be 6 to 12 h. In some other preferred embodiments, the calcination temperature can be 400 to 600 °C, and the calcination time can be 2 to 5 h.
[0024] In some more preferred embodiments, step S1 can include the following process:
[0025] (1) Add Zn(NO 3 ) 2 as the Zn source and the Fe-MCM-41 mesoporous molecular sieve to water with vigorous stirring (for example, 1000 to 1500 rpm) to form an aqueous solution, and continue to stir for 3 to 5 h after adding;
[0026] (2) Transfer the stirred solution system into a hydrothermal reactor for hydrothermal reaction. The reaction temperature can be 100 - 150 °C (preferably 110 - 130 °C), and the reaction time can be 6 - 12 h (preferably 6 - 10 h);
[0027] (3) After separating and washing the solid obtained from the hydrothermal reaction, calcine it in a muffle furnace to obtain the product.
[0028] In the preparation method provided by the present invention, in step S2, IrCl 3 and PdCl 2 are used as the Ir source and Pd source respectively, and polyethylene glycol is used as the dispersant. The Ir / Pd composite oxide is prepared by the co - precipitation - calcination method. In some preferred embodiments, in step S2, the dispersant is dissolved in water and the pH value of the obtained solution is adjusted to 5 - 6. Then the Ir source and Pd source are added, and then alkali is added to adjust the pH value to 10 - 11. The obtained solid is separated and calcined at 500 - 800 °C for 4 - 6 h to obtain the product.
[0029] In some more preferred embodiments, the preparation of the Ir / Pd composite oxide may include the following process: Dissolve the dispersant polyethylene glycol (for example, it can be polyethylene glycol 400) in water, and adjust the pH value of the obtained solution (for example, using 0.5 - 2 mol / L hydrochloric acid solution) to 5 - 6. Then add IrCl 3 and PdCl 2 , and add alkali (for example, ammonia water with a concentration of 20 - 30 wt%) to adjust the pH value to 10 - 11. The solid is separated, and after drying, it is calcined at 500 - 800 °C for 4 - 6 h to obtain the product.
[0030] In the preparation method provided by the present invention, in step S2, the Ir / Pd composite oxide is loaded on the ZnO layer by the impregnation method. In some preferred embodiments, the Ir / Pd composite oxide and the Fe - MCM - 41 mesoporous molecular sieve treated in step S1 are added to an organic solvent (for example, it can be DMF), stirred until the obtained solution becomes paste - like, and then the organic solvent is dried to obtain the product.
[0031] The present invention also provides the use of the supported catalyst containing the Ir / Pd composite oxide according to any one of the above technical solutions in the catalytic dehydrogenation reaction of cyclododecanol to ketone.
[0032] The present invention also provides a method for dehydrogenating cyclododecanol to ketone, which uses the supported catalyst containing the Ir / Pd composite oxide according to any one of the above technical solutions.
[0033] In some preferred embodiments, the method for dehydrogenating to produce ketone may include the following process: First, the supported catalyst is activated in hydrogen at 220 - 260 °C (for example, it can be 230 - 250 °C) (for example, it can be activated for 10 - 30 h), and then the cyclododecanol dehydrogenation to produce ketone reaction is carried out at 200 - 240 °C (for example, it can be 210 - 230 °C) in the presence of the activated supported catalyst.
[0034] In some more preferred embodiments, the cyclododecanol dehydrogenation to produce ketone reaction can be carried out in an inert atmosphere (for example, it can be a nitrogen atmosphere).
[0035] In some more preferred embodiments, the catalyst space velocity of the supported catalyst can be 0.2 - 0.6 h -1 , for example, it can be 0.5 h -1 .
[0036] The supported catalyst containing Ir / Pd composite oxide provided by the present invention has excellent organic chloride adsorption capacity and catalytic activity through multiple modifications. It can not only maintain excellent cyclododecanol conversion rate and cyclododecanone selectivity, but also resist the poisoning of organic chlorides, and can maintain good catalytic effect during long-term operation. Especially, it can maintain a high cyclododecanone selectivity for a long time. Therefore, the service life of the catalyst is significantly extended, and organic chlorides can also be effectively removed from the reaction system. Thus, the reaction efficiency of the cyclododecanol dehydrogenation to produce ketone reaction can be significantly improved, the reaction cost can be reduced, and the stability and controllability of the process can be improved. The preparation process of the supported catalyst provided by the present invention is simple and does not require high cost, which is beneficial to industrial production. Therefore, it has important economic and social values. Detailed Embodiments
[0037] The technical solutions of the present invention will be further described in detail below in conjunction with specific embodiments.
[0038] The conditions for X-ray fluorescence (XRF) analysis used in the examples and comparative examples of the present invention are as follows:
[0039] Instrument model: Jiangsu Tianrui EDX1800BS.
[0040] Analysis method: External standard method.
[0041] The conditions for chromatographic analysis used in the examples and comparative examples of the present invention are as follows:
[0042] Instrument model: Shimadzu GC2010.
[0043] Chromatographic column: DB-5 (30×0.32×0.25); Column temperature: Programmed temperature rise (maintained at 50 °C for 2 min, then increased at a rate of 5 °C / min to 80 °C, and then increased at a rate of 15 °C / min to 280 °C and maintained for 10 min); Injection port temperature: 250 °C; FID temperature: 300 °C; N 2 Flow rate: 1 mL / min; H 2 Flow rate: 40 mL / min; Septum purge (N 2 ) Flow rate: 3 mL / min; Carrier gas (N 2 ) Flow rate: 1 mL / min; Split injection, split ratio: 50; Injection volume: 0.2 μL.
[0044] Analysis method: External standard method.
[0045] Unless otherwise specified, the raw materials or reagents used in the examples and comparative examples of the present invention are all commercially available products.
[0046] Unless otherwise specified, the percentages used in the examples and comparative examples of the present invention are all mass percentages.
[0047] Example 1
[0048] Add 250 g of sodium silicate to 250 mL of deionized water, stir and dissolve at room temperature for 4 h to obtain solution A; Add 64 g of CTAB (template agent) and 10 g of Fe(NO 3 ) 2 ·6H 2 O to 250 mL of deionized water, heat to 90 °C, and stir until dissolved to obtain solution B. After solution B is cooled, add solution A to B, slowly dropwise add 1 mol / L of H 2 SO 4 until the solution pH is 10 to obtain solution C. Continuously stir, after solution C is continuously stirred for 0.5 h, transfer solution C to a stainless steel autoclave, and carry out hydrothermal reaction at 120 °C for 24 h. After the reaction is completed, cool the hydrothermal reaction solution to room temperature and then filter it. Wash the solid with water until the pH is neutral and then dry it to obtain a white solid doped with some green. After grinding the solid into powder, in order to remove CTAB, place the powder in an open-top muffle furnace and calcine at 600 °C for 3 h to obtain 30 g of mesoporous molecular sieve (average particle size about 30 nm) "Fe-MCM-41" with pores modified by iron.
[0049] Add 20 g of Zn(NO 3 ) 2 ·6H 250 g of Fe-MCM-41 was slowly added to a reactor pre-filled with 500 mL of distilled water. During the addition process, vigorous stirring (1000 rpm - 1500 rpm) was carried out. After the addition was completed, stirring continued for about 5 h. Then the product was poured into a hydrothermal reaction kettle, and the reaction kettle was placed in an oven for hydrothermal reaction at 120 °C for 8 h. It was filtered, washed, dried, ground, and calcined in a muffle furnace at 500 °C for 3 h. Finally, 40 g of the composite molecular sieve modified with the additive was obtained and named "Z-MCM-41".
[0050] 50 mL of polyethylene glycol 400 was dissolved in 100 mL of distilled water, and 1 mol / L hydrochloric acid was added to adjust the pH to 5 - 6. Subsequently, 0.78 g of IrCl 3 and 1.38 g of PdCl 2 were added. 25% ammonia water was added dropwise to adjust the pH value to 10 - 11. It was centrifuged at 8000 rpm to remove the supernatant, and the remaining solid was dried overnight at 180 °C. Subsequently, it was calcined in a muffle furnace at 600 °C for 6 h. Finally, 1 g of IrO 2 -PdO was obtained.
[0051] 0.5 g of IrO 2 -PdO and 15 g of the composite molecular sieve Z-MCM-41 were placed in 250 mL of DMF, and stirred evenly until the solution became paste-like. It was placed in an oven and dried overnight at 80 °C, and 15 g of the modified molecular sieve Z-MCM@IPF loaded with IrO 2 -PdO was obtained. The catalyst was named S-Z20. The catalyst composition was analyzed by XRF, and the results are shown in Table 1.
[0052] The reaction evaluation was carried out using a fixed-bed reactor. The catalyst was loaded into the reaction tube of the fixed-bed reactor, and the loading amount was 10 g. The feed rate of cyclododecanol (the Cl content in it was analyzed by XRF to be 3 - 5 ppm) in the raw material was 5 g / h. Before introducing the raw material, the catalyst was activated in the reaction tube. The activation conditions were: the reactor pressure was atmospheric pressure, the activation temperature was 240 °C, the hydrogen flow rate was 100 ml / min, and the activation time was 12 h. When carrying out the reaction evaluation, the reactor was at atmospheric pressure, the reaction temperature was 220 °C, and the nitrogen flow rate was 50 ml / min. After the reactor operation was stable, samples were taken from the bottom of the product tank every 12 h for chromatographic analysis of the product composition to analyze the reaction liquid composition. The conversion rate of cyclododecanol was ~95%, and the selectivity of cyclododecanone was ~99%. The specific analysis results are shown in Table 2.
[0053] Example 2
[0054] Except that 30 g of Zn(NO 3 ) 2 ·6H 2 O was used to replace 20 g of Zn(NO 3 ) 2·6H 2 Except for using 40g Zn(NO
[0055] Example 3
[0056] ) 3 ) 2 ·6H 2 O to replace 20g Zn(NO 3 ) 2 ·6H 2 O, the others are the same as Example 1, and the results are shown in Table 1 and Table 2.
[0057] Example 4
[0058] Except for using 40g Zn(NO 3 ) 2 ·6H 2 O to replace 20g Zn(NO 3 ) 2 ·6H 2 O, 0.93g PdCl 2 to replace 1.38g PdCl 2 except, the others are the same as Example 1, and the results are shown in Table 1 and Table 2.
[0059] Example 5
[0060] Except for using 40g Zn(NO 3 ) 2 ·6H 2 O to replace 20g Zn(NO 3 ) 2 ·6H 2 O, 2.31g PdCl 2 to replace 1.38g PdCl 2 except, the others are the same as Example 1, and the results are shown in Table 1 and Table 2.
[0061] Example 6
[0062] Except for using 40g Zn(NO 3 ) 2 ·6H 2 O to replace 20g Zn(NO 3 ) 2 ·6H 2 O, 0.46g PdCl 2 to replace 1.38g PdCl 2 except, the others are the same as Example 1, and the results are shown in Table 1 and Table 2.
[0063] Comparative Example 1
[0064] Prepare the molecular sieve Fe-MCM-41 with iron-modified pores and IrO 2 -PdO according to the same method as in Example 5.
[0065] Take 0.5 g of IrO 2 -PdO and 15 g of the composite molecular sieve Fe-MCM-41 in 250 mL of DMF, stir evenly until the solution becomes paste-like, and place it in an oven to dry overnight at 80 °C to obtain 15 g of the IrO 2 -PdO-loaded catalyst, named "D-FMPD5".
[0066] Carry out reaction evaluation according to the same method as in Example 1, and the results are shown in Table 1 and Table 2.
[0067] Comparative Example 2
[0068] Use the Z-MCM-41 prepared in Example 1 as the catalyst (named "D-FMZ40" in Table 1).
[0069] Carry out reaction evaluation according to the same method as in Example 1, and the results are shown in Table 1 and Table 2.
[0070] Comparative Example 3
[0071] Use the Fe-MCM-41 prepared in Example 1 as the catalyst (named "D-FM" in Table 1). Carry out reaction evaluation according to the same method as in Example 1, and the results are shown in Table 1 and Table 2.
[0072] Comparative Example 4
[0073] Use a commercially available CuZnAl catalyst (purchased from Nanjing Chemical Industry Research and Design Institute).
[0074] Carry out reaction evaluation according to the same method as in Example 1, and the results are shown in Table 1 and Table 2.
[0075] Table 1 Catalyst parameters of examples and comparative examples
[0076]
[0077] Table 2 Reaction evaluation results of examples and comparative examples
[0078]
[0079]
[0080] As can be seen from the results in Table 2, the supported catalyst provided by the present invention has excellent catalytic activity and an extended service life. Even after continuous operation for 1000 h, the catalyst activity does not decrease significantly and still maintains excellent cyclododecanone selectivity. Under the same operating time, the activity of the commonly used CuZnAl catalyst at present decreases significantly.
[0081] In addition, from Comparative Example 2 and Example 1, it can also be seen that in the supported catalyst provided by the present invention, the content of ZnO has an important influence on the service life of the catalyst, indicating that it is the main organic chloride adsorption layer.
[0082] Unless otherwise specified, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0083] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the protection scope of the present invention. Those skilled in the art can make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments but is only defined by the claims.
Claims
1. A supported catalyst containing Ir / Pd composite oxide, characterized in that, using Fe-MCM-41 mesoporous molecular sieve as the carrier, a ZnO layer is loaded on the surface of the carrier, and an Ir / Pd composite oxide layer is loaded on the ZnO layer. The mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer is 30-45:8-20:0.5-3. In the Ir / Pd composite oxide layer, the molar ratio of Ir to Pd is 1:1-8, and in the Fe-MCM-41 mesoporous molecular sieve, the mass percentage content of Fe is 10-25%.
2. The supported catalyst according to claim 1, characterized in that, the mass ratio of the Fe-MCM-41 mesoporous molecular sieve, the ZnO layer, and the Ir / Pd composite oxide layer is 30-40:10-20:0.8-2.
3. The supported catalyst according to claim 1 or 2, characterized in that, in the Ir / Pd composite oxide layer, the molar ratio of Ir to Pd is 1:3-6; and / or in the Fe-MCM-41 mesoporous molecular sieve, the mass percentage content of Fe is 15-20%.
4. A preparation method of the supported catalyst containing Ir / Pd composite oxide according to any one of claims 1-3, characterized in that, comprising the following steps: S1: Using Fe-MCM-41 mesoporous molecular sieve as the carrier, loading a ZnO layer on its surface; and S2: Preparing an Ir / Pd composite oxide and loading it on the ZnO layer to form an Ir / Pd composite oxide layer.
5. The preparation method according to claim 4, characterized in that, In the step S1, sodium silicate is used as the raw material, cetyltrimethylammonium bromide (CTAB) is used as the template agent, and Fe(NO 3 ) 2 is used as the Fe source, and the Fe-MCM-41 mesoporous molecular sieve is prepared by hydrothermal reaction.
6. The preparation method according to claim 5, characterized in that, the temperature of the hydrothermal reaction for preparing the Fe-MCM-41 mesoporous molecular sieve is 100-150 °C, and the reaction time is 20-40 h.
7. The preparation method according to claim 5, characterized in that, after the hydrothermal reaction for preparing the Fe-MCM-41 mesoporous molecular sieve, the template agent is removed by calcination. The calcination temperature is 500-800 °C, and the calcination time is 2-5 h.
8. The preparation method according to claim 4, characterized in that, In the step S1, Zn(NO 3 ) 2 is used as the Zn source, and it is subjected to a hydrothermal reaction with the Fe-MCM-41 mesoporous molecular sieve, and then calcined to load the ZnO layer.
9. The preparation method according to claim 8, characterized in that, the temperature of the hydrothermal reaction of the Zn source and the Fe-MCM-41 mesoporous molecular sieve is 100-150 °C, and the reaction time is 6-12 h.
10. The preparation method according to claim 8, characterized in that, the calcination temperature is 400-600 °C, and the calcination time is 2-5 h.
11. The preparation method according to claim 4, characterized in that, In the step S2, IrCl 3 and PdCl 2 are used as the Ir source and the Pd source respectively, and polyethylene glycol is used as a dispersant, and the Ir / Pd composite oxide is prepared by a co-precipitation-calcination method.
12. The preparation method according to claim 11, characterized in that, the preparation process of the Ir / Pd composite oxide is: dissolving the dispersant in water and adjusting the pH value of the obtained solution to 5-6, adding the Ir source and Pd source, then adding alkali to adjust the pH value to 10-11, separating the obtained solid, and calcining at 500-800 °C for 4-6 h to obtain.
13. The preparation method according to any one of claims 4 - 12, characterized in that, in the step S2, the Ir / Pd composite oxide is loaded on the ZnO layer by an impregnation method.
14. The preparation method according to claim 13, characterized in that, the process of loading the Ir / Pd composite oxide on the ZnO layer is as follows: adding the Ir / Pd composite oxide and the Fe-MCM-41 mesoporous molecular sieve treated in step S1 into an organic solvent, stirring until the obtained solution becomes paste-like, and drying the organic solvent to obtain the product.
15. Use of the supported catalyst containing Ir / Pd composite oxide according to any one of claims 1 - 3 in the reaction of catalytic dehydrogenation of cyclododecanol to ketone.
16. A method for dehydrogenating cyclododecanol to ketone, characterized in that, the method uses the supported catalyst containing Ir / Pd composite oxide according to any one of claims 1 - 3.
17. The method according to claim 16, characterized in that, the method comprises: first activating the supported catalyst in hydrogen at 220 - 260 °C, and then carrying out the reaction of dehydrogenating cyclododecanol to ketone at 200 - 240 °C in the presence of the activated supported catalyst.
18. The method according to claim 17, characterized in that, The space velocity of the supported catalyst is 0.3 to 0.6 h -1 .
19. The method according to claim 17, characterized in that, the supported catalyst is activated in hydrogen for 10 - 30 h.
20. The method according to claim 17, characterized in that, the reaction of dehydrogenating cyclododecanol to ketone is carried out in an inert atmosphere.
Citation Information
Patent Citations
Catalyst for preparing ketone via cyclododecanol dehydrogenation and preparation method for same
CN103055880A
Method for the production of cyclic ketones
CN101479226A
Mesoporous material with active metals
US20060052234A1